Actively Participating in University-Sponsored Ecological Research Increases High School Students’ Knowledge of and Attitudes About Science - Rollwagen-Bollens, Gretchen; Holmlund, Tamara; Wait, Jude (Frontiers in Environmental Science, 2022)
The Next Generation Science Standards call for students to “investigate the natural world through the processes of scientific inquiry.” Yet, it is rare for secondary students in the U.S. to engage in authentic scientific investigations of natural phenomena. The Columbia River Estuary Science Education and Outreach (CRESCENDO) Project was a two-year (2016 – 2018) university-high school partnership between scientists and science education researchers from Washington State University (WSU) and science teachers and students from five public high schools located adjacent to the Columbia River Estuary (CRE). The teachers and students collaborated with WSU scientists on a rigorous ecological study of the CRE, which provided an opportunity to study how engaging students in authentic scientific research would impact their ecological knowledge and their attitudes toward environmental stewardship. Our study methods included online attitude surveys and knowledge assessments for all participating students, classroom observations, and semi-structured small group interviews with 3-5 students from each school at the end of each year of the project. We found that students made significant gains in their ecological knowledge and understanding of scientific inquiry practices, demonstrating deeper understanding of the connections between local land use and water quality in the CRE, as well how nutrient concentrations vary seasonally and along the axis of the estuary. Students also showed enthusiasm for taking part in a “real” scientific research project, collaborating with university scientists, contributing “their” data to an investigative effort that extended beyond their own school, and the opportunity to get outdoors during science class. We identified five “key elements” of the CRESCENDO project that contributed to its success, and which would allow our model of a consistent, long-term (months) and immersive research experience for high school students to be transferrable to university-school partnerships across a range of size, location, research mission, and resource availability. Finally, this project also provided more evidence in support of place-based approaches for student learning, and the importance of immersing students in their environments where they can study the natural world by asking relevant questions and generating novel data about the science topics that matter to them.